Pengajaran, Penelitian, dan Pelayanan Farmakologi Klinik di Fakultas Kedokteran Negara Berkembang: Teaching, Research, and Service of Clinical Pharmacology in Medical Schools in Developing Countries - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Inadequate access to essential medicines and irrational drug use is commonly practiced, especially in developing countries. The roles of educational institutions are well recognized, but so far there is enough information available about activities of pharmacology or clinical pharmacology departments in improving this situation. This study was conducted to describe teaching, research and service activities of clinical pharmacology in developing countries. One hundred seventy two medical schools in developing countries were surveyed by mean of questionnaire to pharmacology or clinical pharmacology department, and 30 departments responded (15 from Indonesia and 15 from other countries i.e. Malaysia, Philippine, Ghana, South Asia, India, Uganda, Ethiopia, Nepal, Nigeria, Fiji, Argentina, Croatia, and Turkey). Based on the responses, it was found that WHO Guide to Good Prescribing (GGP) has been implemented in 47% and 93% department in Indonesia and other developing countries, respectively. While GGP is an ideal model for integrated teaching, data showed that the integrated teaching with other department was only conducted in 47% departments. Although all department stated that pharmacology was covered, this study found some essential topic which are less covered in the curriculum, e.g., drug utilization problem and factor influencing prescribing, rules and regulation affecting prescription (national drug policy, formulary, standard treatment guideline, essential drug program), ethical and legal aspect of prescribing, clinical trial assessment, clinical pharmacokinetic, and communication skills. Research in clinical pharmacology has been conducted at most departments (93%) mainly in the areas of drug use study (63%), emphasized on identifying drug use problem (53%). A few collaboration with health managers, hospital drug and therapeutic committees and drug industries need more attention. In term of services, only 20% departments in Indonesia and 27% in other developing countries build networking with health manager at district level in improving drug use programmes. In summary,41e data showed that not much effort have been taken by medical schools through teaching, research and service activities of clinical pharmacology to ensure accessibility, affordability and appropriate use of essential medicines in the community. Therefore, intensity of activities and collaboration with relevant stakeholders should be encouraged.